The Internationalization of AccorHotels in South America: why and how? - Wendling, Julien Gauthier (2018)
The tourism industry has been booming worldwide over the last decades, and South America has not been an exception. According to the data provided by the UNWTO, the continent had one of the highest growth in terms of international arrivals in 2017. However, in parallel with this positive trend, some South American countries have been prey to a gloomy economic situation and political turmoil. In spite of these negative aspects, the French multinational hotel chain AccorHotels has always focused significantly on the region. In light of this a priori unintuitive phenomenon, the present research aims at identifying the reasons for AccorHotels’ internationalization in South America, along with the way the process has been carried out, from its arrival in Brazil in 1997 until nowadays. After reviewing the literature about internationalization strategies (especially within the hospitality sector), more specific data has been collected about the history and business strategies of AccorHotels in the frame of a single case study. These include secondary data retrieved from various written sources, but also primary data from the interviews of company’s managers and hospitality experts. In particular, three countries have been considered for this study, corresponding to AccorHotels’ main markets: Brazil (where the South American headquarters are located), Chile and Argentina. The results showed that the main drivers for the internationalization in South America were the economic potential of the countries and the various business opportunities available, coupled with the numerous business-related competences of the group, including experience, flexibility and strong business acumen. As for the expansion process, the eclectic paradigm best describes the internationalization of AccorHotels, and management contracts are the preferred entry modes for the group, due to the great balance between control, risk reduction and (lower) amount of investment. Since little research has been done so far about the internationalization of services companies – especially in the hospitality industry –, this dissertation provides updated material about the situation in these fields. As for managers, this work may provide them with a global overview of AccorHotels’ expansion over the years, and may help strategic actors from hotel chains to better understand the way the South American hospitality market works.